The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1515/jcim-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of piperine and quercetin on antidiabetic potential of curcumin

Abstract: Treatment with combinatorial extract of curcumin presented a significantly better therapeutic potential when compared with curcumin alone, which reveals that CPQ, with reduced dose of curcumin may serve as a therapeutic agent in the treatment of type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The co-administration of curcumin with a bioenhancer (piperine), to increase curcumin bioavailability, did not make curcumin any more efficient in regards to its antidiabetic and antioxidant effects [30]. Adding quercetin to orally administered curcumin can have a better effect on improving the glycemia and lipid profile in STZ-induced diabetes in rats [88]. TAC has shown no significant differences between study groups (with curcumin pre-treatment, Table 1, Figure 2), probably due to a different anti-oxidant system, as components of anti-oxidative status, that remained unchanged after these doses of i.p.…”
Section: Discussionmentioning
confidence: 99%
“…The co-administration of curcumin with a bioenhancer (piperine), to increase curcumin bioavailability, did not make curcumin any more efficient in regards to its antidiabetic and antioxidant effects [30]. Adding quercetin to orally administered curcumin can have a better effect on improving the glycemia and lipid profile in STZ-induced diabetes in rats [88]. TAC has shown no significant differences between study groups (with curcumin pre-treatment, Table 1, Figure 2), probably due to a different anti-oxidant system, as components of anti-oxidative status, that remained unchanged after these doses of i.p.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, piperine promotes glucose uptake in skeletal muscles via ROS‐dependent activation of CAMMK/AMPK signaling pathway (Maeda et al, 2018). Treatment of diabetic rats with piperine caused a significant decrease in the concentration of blood sugar and increased insulin secretion (Kaur et al, 2016). It has also been reported that piperine and curcuminoids control the energy metabolism via modulation of adipokines in type 2 diabetes mellitus (Panahi et al, 2017).…”
Section: Health Perspectivesmentioning
confidence: 99%
“…From this observation, it can be stated that subeffective NF doses of bioactive compounds had no apparent effect on the antidiabetic parameters studied, while combined NF doses exhibited significant antidiabetic effects, possibly due to enhanced absorption of NFs in the circulation. Another reason for improved antidiabetic activity is the synergistic effect of two NFs, which ultimately enhanced pharmacological activity, as supported by the literature 9,10…”
Section: Discussionmentioning
confidence: 81%
“…A combination therapy of rutin and silymarin in streptozotocin (STZ)-induced diabetic rats for 6 weeks reduced plasma-glucose levels and significantly increased antioxidant activity in diabetic rats 9. Kaur et al10 reported the influence of piperine and quercetin on the antidiabetic potential of curcumin, and found that a combination of the three had significant therapeutic potential when compared with curcumin alone. Therefore, the combinational intake of these with foods or synergistic efficacy of these bioactive compounds will be a future research area in diabetic disease management.…”
Section: Introductionmentioning
confidence: 99%